Faculty Collective Bargaining: The Voice of Experience - Ponak, Allen; Thompson, Mark (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
This paper examines the opinions of faculty members who work under collective bargaining regimes. It reports the results of a survey distributed at six Canadian universities where collective bargaining is in place and the faculty in a position tojudge its impact.